Generation and analysis of innovative genomically humanized knockin SOD1, TARDBP (TDP-43), and FUS mouse models - Anny Devoy (Elsevier, 2021)
Summary: Amyotrophic lateral sclerosis/frontotemporal dementia (ALS/FTD) is a fatal neurodegenerative disorder, and continued innovation is needed for improved understanding and for developing therapeutics. We have created next-generation genomically humanized knockin mouse models, by replacing the mouse genomic region of Sod1, Tardbp (TDP-43), and Fus, with their human orthologs, preserving human protein biochemistry and splicing with exons and introns intact. We establish a new standard of large knockin allele quality control, demonstrating the utility of indirect capture for enrichment of a genomic region of interest followed by Oxford Nanopore sequencing. Extensive analysis shows that homozygous humanized animals only express human protein at endogenous levels. Characterization of humanized FUS animals showed that they are phenotypically normal throughout their lifespan. These humanized strains are vital for preclinical assessment of interventions and serve as templates for the addition of coding or non-coding human ALS/FTD mutations to dissect disease pathomechanisms, in a physiological context.